Parent–Child Relationships in the Puberty Years: Insights From Developmental Neuroscience. Issue 3 (6th June 2019) - Suleiman, Ahna Ballonoff; Dahl, Ronald
Abstract : Pubertal maturation creates dynamic changes in parent–child relationships. For many parents, transitioning from parenting a child to parenting an adolescent can create stress, uncertainty, and vulnerability. In this article, we use a developmental science lens to examine the unique opportunities created by this period of dynamic growth, development, and change. We provide a brief overview of emerging research in social and affective neuroscience that examines how pubertal maturation initiates a cascade of adaptive and transformative neurodevelopmental transitions. We consider both challenges and opportunities in the parent–child relationship created by these transitions, highlight how effective parenting during this key developmental window can help establish positive trajectories throughout adolescence, and offer recommendations for both further understanding this transition and improving the precision and scope of resources intended to enhance parents' skills in the context of this transition.